Sol-Gel Method (IntechOpen, 2023)
Synthesizing materials with specific dimensions and properties via a cost-effective approach has long been a major concern among researchers. As such, much research has focused on improving existing synthesis methods or developing new ones. Among the various existing methods, the sol–gel process has been used to synthesize materials for around 100 years. It has recently gained popularity with the evolution of nanoscience and nanotechnology, as it plays a vital role in growing different types of nanostructures, including nanoparticles, thin films, nanotubes, nanorods, nanowalls, and more. The sol–gel process has proven to be a cost-effective, reliable, and reproducible method. This book provides a comprehensive overview of the sol–gel process. It is organized into three sections on the basics and fundamentals of the process, the synthesis of selected materials using the sol–gel method, and the applications of these created materials.